Practice and Perception of Parental HIV Disclosure to Children in Beijing, China - Qiao, Shan (Qual Health Res, 2014)
To explore parental disclosure practices and perceptions among HIV-positive parents in urban China, we conducted in-depth interviews with 29 HIV-positive parents in Beijing in 2011. The disclosure rate was low (17%), and unplanned disclosure was common. Most parents chose not to disclose because of concerns regarding their children’s young age, concerns about potentially negative psychological impacts on the children, potential secondary disclosure by the children to others, and perceived stigma associated with HIV infection and the causes of such infection (e.g., homosexual behaviors). Parents considered that an appropriate disclosure should be well-planned, cautious, and a gradual process conducted in a comfortable and relaxed environment when both parents and children were calm. We concluded that it was important to (a) provide professional guidance and services about disclosure to children for HIV-positive parents in China, (b) reduce or eliminate HIV-related stigma, (c) set up support groups among HIV-positive parents, and (d) tailor disclosure strategies for different populations of various demographic and socioeconomic characteristics.